Quality transplants – a healthy way of raising vegetable nursery - Chaurasia, S.N. S.; Singh, B. (Indian Horticulture, 2019)
A number of vegetable crops of rabi and zaid season are cultivated by transplanting method, wherein seeds are first sown in nursery-beds to raise seedlings and then seedlings are being transplanted in the main field. During the process of seedling raising, the newly born tiny plants get damaged due to certain biotic and abiotic factors. Sometimes, seedlings become very thin due to faulty method of raising seedlings for transplanting in the main field resulting in low yield and less profit. Raising healthy vegetable nursery is an option for achieving higher yield and profit.